Combined experimental studies and theoretical calculations to yield the complete molecular structure and vibrational spectra of (CH3)3GeH - Roldan, Maria Lorena (2009)
The molecular structure of trimethylgermane has been determined by gas electron diffraction experiments. Infrared spectra for the gaseous, liquid, and solid phases were also recorded. Parallel and perpendicular polarized Raman spectra for the liquid were measured to obtain depolarization values. The experimental studies were supported by a series of computational calculations using HF, B3LYP, and MP2 methods and a variety of basis sets. The force fields obtained from density functional theory using both B3LYP/6-31G; and B3LYP/ 6-311+G; ; were scaled with both Pulay's SQM methodology and Yoshida's WLS procedure to simulate the vibrational spectra and assist in the assignment of fundamental bands. The Raman intensities were obtained from polarizability derivatives. The vibrational spectra of trimethylgermane were completely assigned on the basis of the experimental data and the theoretical prediction of vibrational frequencies and intensities.